The fear of Muslims: the inhospitable social space for migrants - Souza, Felipe Freitas de (FCL-UNESP Laboratório Editorial, 2021)
The contemporary social space in large western cities accepts Muslims who are in a refugee situation or migration. Along with the global transformations brought about by different dynamics, Islamophobia arises as a discourse and practice about these populations. The aim of this article is to discuss representations about Muslims in a situation of refuge taking four recent events in the decade of 2010 involving the right and the extreme right as representative: the attack by Anders Breivik in Norway; the demonstration of the Direita São Paulo group in the state capital; the demonstration of the Geração de Mártires group in Rio de Janeiro; and the terrorist attack on a mosque in Christchurch, New Zealand. We point the internet as a means of projecting anti-Islam and anti-refugee discourses. We conclude that Islamophobia, as a mentality, must be problematized, since xenophobia towards Muslims is socially stimulated rather than resulting exclusively from psychological processes.